Implementasi Observasi Profiling Peserta Didik sebagai Persiapan Perencanaan Pembelajaran di Kelas IB SDN Gayamsari 02 Semarang - Nurhayati, Novi; Siswanto, Joko; Nyoman, Ngurah; Isnuryantono, Effendi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study aimed to (1) map the learning styles of students in class IB at SDN Gayamsari 02 Semarang, and (2) design a learning approach aligned with the observed student profiles. The research method used was descriptive qualitative. The population in this study included all grade 1 students at SD Negeri Gayamsari 02 Semarang, with the research sample being Class IB, consisting of 26 students, 13 female and 13 male. The research stages involved planning, implementation, and reflection. Observation results indicated that the designed learning approach did not effectively accommodate the diverse student characteristics in the class. Preparation of the learning design began with observing student profiles, mapping learning styles, and planning methods and approaches in line with all student learning modalities. The learning design included the use of the Teaching at The Right Level (TaRL) approach, the Problem Based Learning (PBL) model, and the Timeboard media in class IB at SD Negeri Gayamsari 02 Semarang. Reflection activities were conducted to identify and evaluate inappropriate learning designs.